The Analysis of Employee Experience, Employee Engagement, and Turnover Intention at XYZ Aesthetic Clinic - Putty Erwina (Research Synergy Foundation, 2022)
XYZ Clinic is a beauty clinic business located in South Jakarta, which has been established for more than 10 years and is still operating today. The development of the beauty business in Indonesia is increasing rapidly, especially skin care products. This can be an opportunity or a threat, depending on how each company responds to the dynamic and uncertain era of the business industry. There are many companies that make employees as internal forces in the face of today's competition, but it will be in vain if superior employees cannot survive and eventually switch to other companies. One of the problems that are often faced is the high Turnover Intention at XYZ Clinic with the highest turnover value in 2020, which is 36.4%. As a result of changing XYZ Clinic, they often lose their superior employees and this is very detrimental to the company. Therefore, the purpose of this research is to analyze Employee Experience, Employee Engagement, and Turnover Intention at XYZ Clinic. To find out what factors encourage having a good employee experience, a more appropriate relationship with the company, and the employee's intention to stay so that this business problem can be solved with the solutions provided by the researcher based on the results of this study. The method used is a mixed method, the first stage is quantitative and the second stage is qualitative as data support.